Comparison of Preauricular Approach Versus Retromandibular Approach in Management of Condylar Fractures - Mohan, A. P. (Springer-Verlag, 2012)
AIM: The aim of the study is to compare the two extra oral approaches to the TMJ viz preauricular and retromandibular approach in management of condylar fractures of mandible. METHODS AND MATERIALS: Patients with fractured dislocation and displacement of mandible condyle in medial direction were managed by preauricular approach. Patients with lateral displacement of mandibular condyle were managed by retromandibular approach. OPG, Reverse towne’s, and C.T. scan were taken in all the cases prior to surgery to assess the pattern of displacement. RESULTS: In our study both approaches have given excellent access and visibility to the condylar fractures but with limitations in each technique. Minimal intraoperative and postoperative complications were encountered in both approaches. The duration of the procedure for preauricular approach was much longer when compared with retromandibular approach. Facial nerve weakness was common in patients treated with preauricular approach, which they improved over a period of time and had complete recovery. Postoperative scar was imperceptible in all cases and good cosmetic results were seen with both approaches. Mouth opening, mandibular movements and occlusion were more or less same in both the approaches while pain and clicking was common in preauricular approach. CONCLUSION: Both approaches have good results in managing condylar fractures with retromandibular approach having ease of access and ease of fixation. So one can always give preference to retromandibular approach over preauricular approach in managing the condylar fracture except in some cases where preauricular approach is the only option like anteromedial dislocation or complete medial dislocation of condylar segment. Situations, where patients who reported very late for the surgery with resultant scarring of the tissue, in those cases preauricular approach is the only option.